2017
DOI: 10.1063/1.4990604
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of higher-order inter-granular exchange in magnetic recording media

Abstract: Exchange coupling between magnetic grains is essential for maintaining the stability of stored information in magnetic recording media. Using an atomistic spin model, we have investigated the coupling between neighbouring magnetic grains where magnetic impurity atoms have migrated into the non-magnetic grain boundary. We find that when the impurity density is low a biquadratic term in addition to the bilinear term is required to properly describe the intergranular exchange coupling. The temperature dependence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Defects present a particular challenge considering dipole fields, since the film morphology can influence the specific characteristics at the nanoscale. In particular orange-peel coupling effects can become important [33] and even percolated exchange coupling [34][35][36]. Future devices utilizing shape anisotropy to enhance thermal stability for sub-20 nm lateral dimensions [37][38][39] rely on a full understanding of dipole interactions at the nanoscale, and so similar atomistic calculation methods presented here can be used to model the role of different physical defects on the effective thermal stability and in particular their switching dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Defects present a particular challenge considering dipole fields, since the film morphology can influence the specific characteristics at the nanoscale. In particular orange-peel coupling effects can become important [33] and even percolated exchange coupling [34][35][36]. Future devices utilizing shape anisotropy to enhance thermal stability for sub-20 nm lateral dimensions [37][38][39] rely on a full understanding of dipole interactions at the nanoscale, and so similar atomistic calculation methods presented here can be used to model the role of different physical defects on the effective thermal stability and in particular their switching dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Ellis et.al. [11] found a similar relation using an atomistic model based on the presence of ferromagnetic impurities in the oxide layer. This study also showed the presence of higher order (biquadratic) exchange and importantly demonstrated that the intergranular exchange decayed to zero rapidly with increasing temperature, suggesting that intergranular exchange does not play a major role in the HAMR recording process.…”
Section: System Energy and Effective Fieldsmentioning
confidence: 60%
“…Atomistic models provide this level of detail and have been used to provide temperature dependent magnetic properties and reversal mechanisms in recording media [5,6,7,8,9,10,11,12,13,14]. Although atomistic simulations can provide exceptional detail of the underlying physical processes which govern their macroscopic properties these simulations carry a significant computational cost.…”
Section: Introductionmentioning
confidence: 99%